Efektivitas Suhu dan Waktu Pengeringan Terhadap Aktivitas Antioksidan dan Sensori Teh Herbal Daun Kirinyuh (Chromolaen odorata L.) - Rahmi, Suci; Susanti, Desi (Agriculture Faculty, 2023)
Kirinyuh leaves (Chromolaen odorata L) contain several main compounds such as tannins, phenols, flavonoids, saponins and steroids. This plant is a wild plant and is easily found in the south west area of the Aceh region, however the kirinyuh leaf has not been used optimally as a functional food ingredient. Therefore, this study will utilize kirinyuh leaves as a dry product, one of which is processing into herbal teas. The drying process of kirinyuh leaves affects the content of chemical compounds contained in a plant, especially compounds that are efficacious as antioxidants. This study aims to obtain the effective temperature and time for drying herbal tea from kirinyuh leaves so as to produce the highest antioxidant activity and sensory quality. The research method used in this study is an experimental method using Completely Randomized Design (CRD) with 2 factors as treatment. Factor I is drying temperature (T) with 3 treatments (40 oC, 50 oC, 60 oC). while factor II is drying time (t) with 3 treatments (1 hour, 2 hours, 3 hours). The treatment was repeated 3 times to obtain 27 observational data. The data obtained were analyzed by means of variance, if there was a significant treatment effect (p 0.05), then continued with Duncan's test or BNT on the average treatment. The results showed that the drying temperature of 60oC has a very strong antioxidant value, the IC50 value is less than 50 ppm (48.08-49.21). The results of the water content test were obtained in the range of 4.90% - 6.33%. The results of the pH test are 5.3 5.5. The results of the sensory analysis showed that the panelists' overall preference (color, taste, aroma) ranged from 2.5 3 (liked enough).